Preparation of NiIn2O4 / CeO2 composite material and application of NiIn2O4 / CeO2 composite material in rifampicin detection

Through NIN2O4 and CEO2, it is aggregated into composite materials to build electrochemical sensors to solve the problems of detecting Liffu's usual materials and high costs in existing technologies. Sexuality and reproduction.

CN119355075APending Publication Date: 2025-01-24GUANGXI NORMAL UNIV FOR NATITIES
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411485170.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art has problems such as high material consumption, high cost, complex technology, and cumbersome maintenance in detecting Rifle. In addition, simple In2O3 and CeO2 are low in response, poor selectivity, and long response recovery time in electrochemical analysis and detection.

Method used

NiIn2O4 and CeO2 are polymerized in situ to form a composite material, nickel-indium oxide (NiIn2O4) is synthesized through solvothermal reaction and calcination method, and NiIn2O4/CeO2 composite material is synthesized under the polymerization catalysis of methenamine for the construction of electrochemical The sensor performs rifampicin detection.

Benefits of technology

The catalytic activity and stability of the material are improved, and rapid and sensitive detection of rifampicin is achieved. It has good sensitivity, reliable reproducibility and high stability, and is suitable for the detection of rifampicin in drugs and serum. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119355075A_ABST
    Figure CN119355075A_ABST
Patent Text Reader

Abstract

The invention discloses preparation of a NiIn2O4 / CeO2 composite material and application of the NiIn2O4 / CeO2 composite material in rifampicin detection, and belongs to the technical field of electrochemical sensing. The preparation method of the NiIn2O4 / CeO2 composite material comprises the following steps: (1) preparing In2O3 from DMF (Dimethyl Formamide), pyridine, indium nitrate hydrate and terephthalic acid; (2) preparing NiIn2O4 by adopting In2O3 and Ni (NO3) 2.6 H2O; and (3) preparing the NiIn2O4 / CeO2 composite material from NiIn2O4, a cerous nitrate solution and a urotropine solution. The NiIn2O4 / CeO2 composite material disclosed by the invention is used for preparing a corresponding electrochemical sensor, and the electrochemical sensor is used for detecting the content of rifampicin and has good sensitivity, reliable reproducibility and relatively high stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical sensing technology, and in particular to NiIn 2 O 4 / CeO 2 Preparation of composite materials and their application in rifampicin detection. Background Art

[0002] Tuberculosis is a chronic disease that has a huge impact on various parts of the body, such as the lungs, liver and spleen, and can cause side effects such as loss of appetite, significant weight loss, chronic fatigue, coughing, coughing up blood, and even fatal side effects such as respiratory failure, sepsis and heart attack.

[0003] Rifampicin, as a semi-synthetic broad-spectrum antibiotic, is widely used in the treatment of diseases in clinical practice. It is a commonly used anti-tuberculosis mycobacterium drug and has significant efficacy against infectious diseases such as leprosy and HIV. However, excessive intake of rifampicin may cause adverse side effects such as hepatotoxicity, dizziness, nausea and rash, and may also cause anorexia, epileptic seizures and renal failure. Therefore, the amount of rifampicin taken by tuberculosis patients during treatment should be controlled, and sensitive and accurate determination of rifampicin is very necessary. According to literature survey, a variety of analytical techniques for the determination of rifampicin have been reported, such as ultraviolet spectrophotometry, chemiluminescence analysis, high performance thin layer chromatography, ultra-high performance liquid chromatography-mass spectrometry, etc. However, these analytical techniques have defects such as high material consumption, high cost, complex technology and cumbersome maintenance. Electrochemical sensing technology has received increasing attention in the field of medical monitoring due to its advantages of high sensitivity, low detection limit and low cost. Rifampicin is rich in phenolic hydroxyl groups and is an electroactive compound that can undergo redox reactions on different working electrodes. Therefore, rifampicin can be analyzed by electrochemical methods.

[0004] In recent years, many materials such as metal and metal oxide nanomaterials, carbon nanomaterials, noble metal nanoparticles and metal organic frameworks have been widely used as electrode materials in sensing monitoring, catalysis, energy and other fields. The latest scientific research progress shows that nanomaterials have excellent performance in drug detection sensor research. They are small in size and can easily penetrate living tissues and cells. Therefore, nanoparticles are often used for early diagnosis of diseases and drug monitoring. Indium oxide (In 2 O 3 ), an n-type semiconductor functional material, has been widely used in the optoelectronic field, gas sensors, catalysts, mercury replacement inhibitors for alkaline manganese batteries, etc. due to its wide band gap, high single crystal mobility and high electrocatalytic activity. However, pure In 2 O 3Low response, poor selectivity, and long response recovery time. 2 ) is a rare earth oxide that is widely used in electrocatalysis due to its excellent redox properties, high stability and good corrosion resistance. 2 Poor conductivity and fewer active sites hinder electron transfer, making it difficult to achieve sensitive and accurate determination of target traces, limiting its application in electrochemical analysis and detection. Summary of the invention

[0005] The present invention is to solve the above technical problems existing in the prior art and provides NiIn 2 O 4 / CeO 2 Preparation of composite materials and their application in rifampicin detection. 2 O 4 With CeO 2 The composite material is polymerized in situ, and due to the synergistic effect between the two, the catalytic activity and stability of the material are greatly improved, which can be applied to the field of electrochemical sensing. The present invention not only develops an efficient electrochemical catalyst, but also provides a new electrochemical sensing platform based on non-precious metal electrocatalysts for detecting rifampicin, which has good sensitivity, reliable reproducibility and high stability.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0007] NiIn 2 O 4 / CeO 2 The method for preparing the composite material comprises the following steps:

[0008] (1) DMF and pyridine are mixed evenly, and then indium nitrate hydrate and terephthalic acid are added, and then stirred after ultrasonication to disperse evenly, and the reaction is continued at 110-130° C. for 20-40 minutes. After the reaction is completed, the suspension is taken out, and the suspension is cooled to room temperature, and the substrate is centrifuged to obtain the substrate, and the obtained precipitate is washed, dried, and calcined to obtain In 2 O 3 ;

[0009] (2)In 2 O 3 and Ni(NO 3 ) 2 6H 2 O was placed in a container, anhydrous ethanol was added, ultrasonic dispersion was uniform, and under continuous stirring, refluxed at 85-95℃ for 1-2h. After the reaction was completed, the suspension was cooled to room temperature, centrifuged to obtain the substrate, washed the obtained precipitate, dried, and calcined to obtain NiIn 2 O 4 ;

[0010] (3) NiIn 2 O 4 Place in a container, add ethanol aqueous solution, disperse evenly by ultrasonication, add cerium nitrate solution and urotropine solution, keep at 50-70℃ for 1-3h, centrifuge to separate the substrate, wash the precipitate, and dry to obtain NiIn 2 O 4 / CeO 2 Composite materials.

[0011] Further, the specific operation steps of step (1) are as follows: 300-500 mL DMF and 0.5-0.6 mL pyridine are added to a container and mixed evenly, and then 0.5-0.8 g In(NO 3 ) 3 ·xH 2 O and 0.5-0.8 g C 8 H 6 O 4 , after ultrasonic treatment for 3-8 minutes, stir for 20-40 minutes to make it dispersed evenly, and continue the reaction at 100-150℃ for 20-50 minutes; after the reaction is completed, take it out and wait for the suspension to cool to room temperature, 4000-6000r·min -1 After centrifugation for 3-8 minutes, the substrate was taken out and the precipitate was washed with water and ethanol for 2-5 times respectively, dried in a vacuum oven at 50-70℃ for 2-5 hours to obtain a white powder, which was then calcined at 3-8℃·min -1 The temperature was raised at a rate of 100-130 °C for 1-3 h, then calcined at 400-600 °C for 1-3 h, and then at 3-8 °C min -1 The temperature was cooled to room temperature at a rate of 2 O 3 .

[0012] Further, the specific operation steps of step (2) are as follows: 90-110 mg In 2 O 3 and 130-160mgNi(NO 3 ) 2 6H 2 O was placed in a container, 40-60 mL of anhydrous ethanol was added, and ultrasonication was performed for 15-30 min to make it evenly dispersed. Under continuous stirring, reflux was performed at 85-95 ° C for 1-2 h. After the reaction was completed, the suspension was cooled to room temperature and the reaction mixture was stirred at 6000-9000 r·min -1 After centrifugation for 3-8 minutes, the substrate was taken out and the precipitate was washed with water and ethanol for 2-5 times, then dried in a vacuum drying oven at 50-70°C for 2-5 hours to obtain a gray-green powder, which was calcined in a tubular furnace under N 2 At 3-8℃·min-1 Increase the temperature at a rate of 300-400℃ for 40-80min, turn off N 2 Valve, calcined in air at 300-400℃ for 40-80min, 3-8℃·min -1 The cooling rate was lowered to room temperature to obtain NiIn 2 O 4 .

[0013] Further, the specific operation steps of step (3) are as follows: weigh 40-60 mg NiIn 2 O 4 Place in a container, add 50-80mL of 50% ethanol aqueous solution, ultrasonicate for 8-15min to make it disperse evenly, and slowly add 8-15mL of 3-8mmol·L -1 8-15mL of cerium nitrate solution and 10-20mmol·L -1 Hexamethylenetetramine solution, maintained at 50-70℃ for 1-3h, 6000-9000r·min -1 Centrifuge for 3-8 minutes to separate the substrate, wash the precipitate with water and ethanol 2-5 times, and dry it in vacuum at 50-70°C for 2-5 hours to obtain NiIn. 2 O 4 / CeO 2 Composite materials.

[0014] NiIn prepared by the above preparation method 2 O 4 / CeO 2 The application of the composite material in the detection of rifampicin is specifically to use the NiIn 2 O 4 / CeO 2 The composite material is used to prepare a corresponding electrochemical sensor, and the electrochemical sensor is used to detect the content of rifampicin.

[0015] Furthermore, the method for detecting the content of rifampicin includes detecting the content of rifampicin in rifampicin eye drops and blood samples.

[0016] Furthermore, the preparation of the electrochemical sensor comprises the following steps: 2 O 4 / CeO 2 Composite materials made of 0.8-1.2 mg·mL -1 NiIn 2 O 4 / CeO 2 Composite material suspension; polish the glassy carbon electrode, clean it, and use N 2 After drying, take NiIn 2 O 4 / CeO 2 The composite material suspension was dripped onto the surface of the glassy carbon electrode and dried naturally to obtain NiIn 2 O 4 / CeO 2 The composite material modified electrode is used as the electrochemical sensor.

[0017] Further, the steps for detecting the content of rifampicin are as follows: NiIn 2 O 4 / CeO 2 The composite material modified electrode was inserted into the test solution, and after incubation for 20 seconds, the rifampicin content was detected by differential pulse voltammetry.

[0018] Furthermore, when detecting the content of rifampicin in a drug, the preparation method of the test solution is as follows: the drug is added to a PBS buffer solution with a pH of 1-3 to prepare a solution containing 0.02 to 82.5 μmol·L -1 Rifampicin concentration base solution;

[0019] Furthermore, when detecting the rifampicin content in a blood sample, the preparation method of the test solution is as follows: serum and anhydrous methanol are taken at a V / V ratio of 1:3, mixed thoroughly and evenly, centrifuged to remove plasma protein precipitate, and an appropriate amount of supernatant is taken, and a PBS buffer solution with a pH of 1-3 is added.

[0020] Furthermore, the medicine is rifampicin eye drops, and the pH of the PBS buffer is 2.5.

[0021] Beneficial effects:

[0022] The present invention adopts solvent thermal reaction and calcination method to synthesize nickel-indium oxide (NiIn 2 O 4 ) was synthesized under the polymerization catalysis of urotropine (hexamethylenetetramine) to synthesize cerium dioxide (CeO 2 ) and NiIn 2 O 4 Composite materials (NiIn 2 O 4 / CeO 2 ), based on NiIn 2 O 4 / CeO 2 An electrochemical sensor was constructed to detect rifampicin. 2 O 4 and CeO 2 The synergistic electrocatalytic activity of rifampicin was remarkable. 2 O 4 / CeO 2The electrochemical redox process of two electrons and two protons occurs on the surface of the modified glassy carbon electrode. The electrochemical sensor is fast and sensitive for detecting rifampicin, and shows excellent performance in the analysis of drugs and serum. The electrochemical sensor shows good sensitivity, reliable reproducibility and high stability, and can be used for the detection of rifampicin in rifampicin eye drops and blood samples. The spike recovery rate ranges from 98.43% to 102.00%, indicating that it has good practical application value in the field of drug analysis.

[0023] In summary, the present invention converts NiIn 2 O 4 With CeO 2 The composite material is polymerized in situ, and due to the synergistic effect between the two, the catalytic activity and stability of the material are greatly improved, and can be applied to the field of electrochemical sensing. The present invention not only develops an efficient electrochemical catalyst, but also provides a new electrochemical sensing platform based on non-precious metal electrocatalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 For NiIn 2 O 4 / CeO 2 Schematic diagram of the synthesis mechanism of / GCE;

[0025] Figure 2 SEM images, in which: (A) In 2 O 3 , (B)NiIn 2 O 4 ,(C)NiIn 2 O 4 / CeO 2 SEM image of the composite material; (D) NiIn 2 O 4 / CeO 2 TEM image of (E) enlarged TEM image; (F) NiIn 2 O 4 / CeO 2 Ce, Ni, In SEM-element distribution map;

[0026] Figure 3 The performance characterization diagram of electrodes modified with different materials, including: (A) electrochemical impedance spectroscopy, (B) CV graph, (C) chrono-Coulomb curve and (D) corresponding Qt 1 / 2 Figure (curve a: bare / GCE, b: In 2 O 3 / GCE,c:NiIn 2 O 4 / GCE,d:NiIn2 O 4 / CeO 2 / GCE);

[0027] Figure 4 For NiIn 2 O 4 / CeO 2 CV graphs of / GCE for rifampicin in PBS buffer solutions with different pH values ​​(1.0-7.0), (B) the relationship between pH and peak current value and potential value;

[0028] Figure 5 For different scan rates (0.1~1.0V·s -1 ) (A) Cyclic voltammogram, (B) Relationship between peak current and scan rate, (C) Relationship between potential and scan rate; (D) Cyclic voltammogram of rifampicin in NiIn 2 O 4 / CeO 2 Diagram of the electrochemical behavior mechanism of the / GCE surface;

[0029] Figure 6 0.02~82.5μmol·L -1 Rifampicin in CeO 2 / NiIn 2 O 4 (A) DPV curves of / GCE surface and (B) corresponding data. DETAILED DESCRIPTION

[0030] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0031] Example

[0032] Instrument preparation:

[0033] Scanning electron microscope (ZEISS, EVO-18, Germany), X-ray photoelectron spectrometer (ThermoScientific K-Alpha, USA); vacuum drying oven (Shanghai Foma Experimental Equipment Co., Ltd., D2x-6050B), electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd., CHI760E), electronic analytical balance (Ohaus Instrument (Shanghai) Co., Ltd., AR124CN); three-electrode system used: glassy carbon electrode (GCE, d = 3 mm) as the working electrode, platinum wire as the auxiliary electrode, and Hg / HgCl electrode as the reference electrode.

[0034] Reagent preparation:

[0035] Rifampicin, indium nitrate hydrate (In(NO 3 ) 3 ·xH 2O), cerium nitrate hydrate (CeN 3 O 9 6H 2 O), terephthalic acid (C 8 H 6 O 4 ), pyridine (C 5 H 5 N), hexamethylenetetramine (hexamethyltetramine, C 6 H 12 N 4 ), N,N-dimethylformamide (DMF) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. PBS was used as the supporting electrolyte, which contained 0.1 mol·L -1 0.2 mol·L KCl -1 NaH 2 PO 4 Solution and 0.20 mol·L -1 Na 2 HPO 4 The solution is mixed and prepared, and if necessary, an appropriate amount of 5.0 mol·L -1 Phosphoric acid solution was used to prepare a series of PBS buffer solutions with different pH values ​​(pH = 1.0, 2.5, 3.0, 3.5, 4.0, 5.0, 6.0, 7.0). Rifampicin eye drops (10 mL, 0.5 mg mL -1 , Wuhan Wujing Pharmaceutical Co., Ltd., batch number: 23060316), and human serum samples were provided free of charge by Chongzuo People's Hospital. Other reagents were of analytical grade, and the experimental water was deionized water.

[0036] NiIn 2 O 4 Preparation:

[0037] 400 mL of DMF and 0.58 mL of pyridine were added to the flask and mixed evenly, and then 0.6 g of In(NO 3 ) 3 ·xH 2 O and 0.6gC 8 H 6 O 4 After ultrasonic treatment for 5 minutes, the suspension was placed on a magnetic stirrer and stirred for 30 minutes to make it evenly dispersed. The reaction was continued at 120°C for 30 minutes. After the reaction was completed, the suspension was taken out and cooled to room temperature. -1 The substrate was taken out after centrifugation for 5 min, and the precipitate was washed with water and ethanol for 3 times respectively, and dried in a vacuum oven at 60°C for 3 h to obtain a white powder, which was placed in a quartz boat and calcined in a tube furnace at 5°C·min -1 The temperature was raised at a rate of 120 °C for 2 h, 500 °C for 2 h, and then at 5 °C min-1 The temperature was cooled to room temperature to obtain a light yellow powder In 2 O 3 .

[0038] 100mg In 2 O 3 and 150mgNi(NO 3 ) 2 6H 2 O was placed in a flask, 50 mL of anhydrous ethanol was added, and ultrasonication was performed for 20 min to make it uniformly dispersed. Under continuous stirring, reflux was performed at 90 ° C for 1.5 h. After the reaction was completed, the suspension was cooled to room temperature and 8000 r / min -1 The substrate was centrifuged for 5 min and the precipitate was washed with water and ethanol for 3 times respectively, and then dried in a vacuum drying oven at 60 °C for 3 h to obtain a gray-green powder, which was calcined in a tubular furnace under N 2 At 5℃·min -1 The temperature was raised to 350 °C for 1 h, and then N 2 Valve, calcined in air at 350℃ for 1h, at 5℃·min -1 The cooling rate was lowered to room temperature to obtain NiIn 2 O 4 .NiIn 2 O 4 / CeO 2 Preparation of composite materials:

[0039] Weigh 50 mg NiIn 2 O 4 Place in a flask, add 60mL of 50% ethanol aqueous solution, ultrasonicate for 10min to make it disperse evenly, and slowly add 10mL of 5mmol·L -1 Cerium nitrate solution (using cerium nitrate hydrate CeN 3 O 9 6H 2 O configuration) and 10mL 15mmol·L -1 Hexamethylenetetramine solution (prepared with hexamethylenetetramine), maintained at 60℃ for 2h, 8000r·min -1 Centrifuge for 5 minutes to separate the substrate, wash the precipitate with water and ethanol three times each, and dry it in vacuum at 60°C for 3 hours to obtain NiIn 2 O 4 / CeO 2 Composite materials.

[0040] Preparation of modified electrode:

[0041] 1mgNiIn 2 O 4 / CeO2 The composite material was added with 1 mL of deionized water and then dispersed evenly by ultrasonication for 20 min to obtain NiIn 2 O 4 / CeO 2 Suspension (1 mg mL -1 ). The glassy carbon electrodes are 1um, 0.5um, and 0.03umAl 2 O 3 After polishing the suede with polishing powder, clean it with deionized water and use N 2 After drying, take 5 μL NiIn 2 O 4 / CeO 2 The composite material suspension was dripped onto the surface of the glassy carbon electrode and dried naturally to obtain NiIn 2 O 4 / CeO 2 Composite modified electrode (NiIn 2 O 4 / CeO 2 / GCE). 2 O 4 / CeO 2 The synthesis mechanism of GCE is as follows Figure 1 As shown. As a comparison, the same method was used to prepare In 2 O 3 / GCE、NiIn 2 O 4 / GCE.

[0042] Preparation of actual sample solution:

[0043] Rifampicin eye drops (labeled amount: 0.5 mg mL -1 ) without any pretreatment, directly pipette 50 μL into 10 mL PBS (pH = 2.5) buffer with a microsyringe to prepare a solution containing about 3.04 μmol·L -1 The base solution for testing rifampicin concentration is reserved.

[0044] Serum sample pretreatment: serum and anhydrous methanol (V / V = 1:3) were mixed thoroughly and heated at 10000 r / min. -1 The plasma protein precipitate was removed, and an appropriate amount of supernatant was taken and added to 10 mL of PBS (pH = 2.5) buffer for testing.

[0045] Electrochemical detection of rifampicin:

[0046] NiIn 2 O 4 / CeO 2 / GCE was inserted into PBS buffer solution containing different concentrations of rifampicin. After incubation for 20 seconds, cyclic voltammetry (CV) and differential pulse voltammetry (DPV) were used to study its electrochemical behavior. Electrochemical impedance spectroscopy was used to study the electrochemical behavior of the GCE at 5 mmol·L -1 Fe[(CN) 6 ] 3- / 4- Solution (containing 0.1 mol·L -1 The working potential was 0.2 V.

[0047] Related tests and results:

[0048] (1) SEM and TEM characterization of electrochemical materials

[0049] Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to characterize the morphology and elements of the synthesized materials. Figure 2 As shown, Figure 2 (A) is In 2 O 3 SEM image of In 2 O 3 It is a nanostructure with uniform size and regular shape; Figure 2 (B) NiIn 2 O 4 SEM images of 2 O 3 After Ni metal doping, bimetallic oxides are formed with little change in shape. Figure 2 (C) is NiIn 2 O 4 / CeO 2 SEM images of the composite materials. Figure 2 (D) and (E) are NiIn 2 O 4 / CeO 2 TEM image of the composite material, composed of NiIn 2 O 4 The size of CeO 2 Should be polygonal nanostructure, NiIn 2 O 4 Nanoparticles are evenly distributed on CeO 2 surface. Figure 2 (F) is NiIn 2 O 4 / CeO 2 The SEM-element distribution diagram shows that Ce, Ni, and In elements are evenly distributed, which indicates that NiIn was successfully synthesized in the experiment. 2 O 4 / CeO 2 Composite materials.

[0050] (2) Characterization of performance of different modified electrodes

[0051] Figure 3 (A) Cyclic voltammetry (CV) was used to study the electrochemical behavior of rifampicin on different modified electrodes. -1 In the PBS (pH = 2.5) solution of rifampicin, obvious redox peaks were shown in the potential range of -0.1 to 0.8 V. Bare glassy carbon electrode (Bare / GCE), In 2 O 3 / GCE、NiIn 2 O 4 / GCE、NiIn 2 O 4 / CeO 2 The oxidation peak currents of / GCE were 1.13μA, 1.62μA, 1.85μA, and 3.20μA, respectively. Bare / GCE showed the smallest peak current, indicating that the monomer material and the composite material have good catalytic activity for Rifampicin. 2 O 4 / GCE shows a peak current higher than In 2 O 3 / GCE is large, indicating that Ni doping makes the material exhibit better electrocatalytic ability. 2 O 4 / CeO 2 / GCE exhibits the largest peak current response, about 3 times that of Bare / GCE. 2 O 4 With CeO 2 After in-situ polymerization, due to the synergistic effect between the two, it has good electrocatalytic ability for rifampicin.

[0052] In the presence of 0.1 mol·L -1 5mmol·L KCl -1 Fe(CN) 6 3- / 4- In the solution, the working potential was 0.2 V, and the difference in electron transfer rate on the surface of different modified electrodes was investigated by electrochemical impedance spectroscopy (EIS). Figure 3 (B) The semicircular cross section in the high-frequency region represents the charge transfer limitation process, and its diameter is the charge transfer resistance (R et ), R of each material modified electrode et Size is NiIn 2 O 4 / CeO 2 / GCE>Bare / GCE>In 2 O 3 / GCE>NiIn2 O 4 / GCE. Zview software was used for fitting, R et The values ​​are 1750Ω, 1570Ω, 876Ω, and 394Ω respectively. 2 O 3 Has good electrical conductivity, thus exhibiting a small R et , after Ni doping R et becomes smaller, proving that the electron transfer rate on the material surface is accelerated, indicating that NiIn 2 O 4 was successfully synthesized. 2 The band gap between electrons is large, usually requiring higher energy to be excited, and the conductivity is poor, resulting in NiIn 2 O 4 / CeO 2 R et This further indicates that NiIn was successfully synthesized. 2 O 4 / CeO 2 In addition, at 1mmol·L -1 [Fe(CN) 6 ] 3- / 4- In this paper, the chrono-coulometry method was used to study the relationship between charge (Q) and potential pulse width (t), Q and t 1 / 2 The relationship between (r represents the correlation coefficient), such as Figure 3 (C) and (D). Bare / GCE, In 2 O 3 / GCE、NiIn 2 O 4 / GCE、NiIn 2 O 4 / CeO 2 Qt for GCE 1 / 2 The relationship equations are:

[0053] Q(μC)=62.16t 1 / 2 (s 1 / 2 )+7.21(r=0.9975)

[0054] Q(μC)=66.12t 1 / 2 (s 1 / 2 )+17.74(r=0.9955)

[0055] Q(μC)=32.78t 1 / 2 (s 1 / 2 )+4.99(r=0.9976)

[0056] Q(μC)=101.57t 1 / 2(s 1 / 2 )+7.70(r=0.9959)

[0057] According to the following Anson formula:

[0058]

[0059] n represents the number of electron transfers, 1; F is the Faraday constant, 96,485 C·mol -1 ; A is the effective working area; C is the solution concentration, 1mmol·L -1 ; D is the diffusion coefficient, 7.6×10 -6 cm 2 ·s -1 ; The calculated effective areas of the electrodes are 0.21 cm 2 、0.22cm 2 、0.11cm 2 、0.34cm 2 The results show that CeO 2 Effectively polymerized NiIn 2 O 4 The synergistic effect of the two leads to an increase in the effective area of ​​the composite material, thereby showing more active sites, which is more conducive to the efficient and sensitive detection of rifampicin.

[0060] (3) pH of PBS buffer solution

[0061] Differential pulse voltammetry (DPV) was used to investigate the 2 O 4 / CeO 2 The effect of pH on the peak current of GCE in PBS buffer solutions with different pH values ​​(pH = 1.0, 2.5, 3.0, 3.5, 4.0, 5.0, 6.0, 7.0) was investigated in the potential range of -0.4 to 0.6 V. The results are as follows Figure 4 (A) and (B). In the pH range of 1.0 to 7.0, the potential of the oxidation peak decreases with increasing pH, indicating that protons participate in the electrochemical reaction. Rifampicin contains multiple phenolic hydroxyl groups. Under alkaline conditions, due to the lack of protons, the electrochemical reaction is difficult and the peak current response is poor. In pH = 2.5 PBS buffer solution, the peak current reaches the maximum value. As the pH value of the PBS buffer solution gradually increases, the electrochemical potential of the oxidation peak gradually decreases and shows a good linear relationship. The linear equation is E pa =-0.0544pH+1.01(r=0.9855), the absolute value of the slope (54.4mV·pH -1 ) is close to the Nernst theoretical value (59.2mV·pH -1), indicating that the number of electrons (n) and protons (m) transferred in the electrochemical reaction of rifampicin are equal.

[0062] (4) Scan rate

[0063] Figure 5 (A) is the concentration of 30 μmol·L -1 Rifampicin in PBS buffer solution, at 0.1~1.0V·s -1 CV curves at different scan rates within the range. Figure 5 (B) As shown in the results, the redox peak current gradually increases with the increase of scanning rate, and the oxidation peak current (I pa ), reduction peak current (I pc ) and v show a good linear relationship, and the linear equations are:

[0064] I pa (μA)=5.24v(V·s -1 )+0.67(r=0.9990)

[0065] I pc (μA)=2.72v(V·s -1 )+0.43(r=0.9926).

[0066] Description Rifampicin in NiIn 2 O 4 / CeO 2 The reactions occurring on the / GCE surface are controlled by adsorption. Figure 5 (C) is the oxidation peak potential (E pa ), reduction peak potential (E pc ) and the natural logarithm of the scan rate (lnv), the linear regression equations are:

[0067] E pa (V) = 4.44 × 10 -2 lnv(V·s -1 )+0.42(r=0.9984)

[0068] E pc (V) = -2.17 × 10 -2 lnv(V·s -1 )+0.13(r=0.9940)

[0069] According to the Laviron equation:

[0070]

[0071] R is the ideal gas constant, 8.314 J·(mol·K) -1; T is the thermodynamic temperature, 298.15K; F is the Faraday constant, 96,485C·mol -1 ; α is the charge transfer coefficient, n is the charge transfer number. It can be calculated that α = 0.67, n = 1.75 ≈ 2, which shows that rifampicin in NiIn 2 O 4 / CeO 2 The electrochemical redox process on the surface of / GCE involves 2 electrons and 2 protons (m=n=2), from which the reaction equation of rifampicin on the electrode is inferred, such as Figure 5 As shown in (D), first, in the single electron transfer process of rifampicin, the electrochemical oxidation of the phenolic hydroxyl group produces rifampicin semiquinone free radicals, which then rapidly undergo disproportionation reactions. Due to the high activity of the rifampicin semiquinone free radicals, the products are rapidly converted into quinone-type rifampicin products.

[0072] (5) Detection of Rifampicin

[0073] In pH = 2.5 PBS buffer solution, differential pulse voltammetry (DPV) was used to study the effect of different concentrations of rifampicin on the oxidation peak current. As the concentration of rifampicin increased, the peak current value gradually increased. Figure 6 (A). 0.02~82.5μmol·L -1 The electrical signal within the concentration range showed good linearity, and the linear equation was expressed as Ip (μA) = 0.0307C (μmol·L -1 )+0.053(r=0.9985), such as Figure 6 (B), detection limit is 2.54nmol·L -1 Compared with the existing method for detecting rifampicin, the method of the present invention shows the advantages of a wider linear range and a lower detection limit for rifampicin (see Table 1).

[0074] Table 1 Comparison of results of rifampicin determination methods

[0075]

[0076] Note: a Nickel hexacyanoferrate nanomaterials; b Bismuth vanadate microspheres; c Reduction of graphene oxide nanosheets by nickel hydroxide nanoparticles; d Quinoxaline-based conjugated microporous polymer grafted onto graphene; e Folic acid-protected copper nanoclusters; f Nitrogen and sulfur co-doped carbon dots;

[0077] g Square wave voltammetry.

[0078] [1]Oliveira P.R.,Schibelbain A.F.,Eduardo G.C.,et al.Nickelhexacyanoferrate supported at nickel nanoparticles for voltammetricdetermination of rifampicin[J].Sens.Actuators.B.,2018,260:816-823;

[0079] [2]Vinothkumar V.,Sangili A.,Chen S.,et al.Additive-free synthesisofBiVO4 microspheres as an electrochemical sensor for determination ofantituberculosis drug rifampicin[J].Colloids Surf.,A,2021,264:126849;

[0080] [3]Rastgar S.,Shahrokhian S.Nickel hydroxide nanoparticles-reducedgraphene oxide nanosheets film:Layer-by-layer electrochemical preparation,c-haracterization and rifampicin sensory application[J].Talanta,2014,119:156-163;

[0081] [4]Xiang G.,He X.,Zhuge W.,et al.Quinoxaline-based conjugatedmicroporous polymer-grafted graphene sensors for the sensitive detectionofrifampicin[J].Microchem.J.,2023,190:108595;

[0082] [5] Liu J., Sun J., Zhang W., et al. HPLC determination of rifampicin and related compounds in pharmaceuticals using monolithic column [J]. J. Pharm. Biomed. Anal., 2008, 46 (2): 405-409;

[0083] [6]Zhang Y., Deng Q., Tang C., et al.Fluorescent folic acid-cappedcopper nanoclusters for the determination of rifampicin based on inner filtereffect[J].Spectrochim.Acta,Part A,2023,286:121944;

[0084] [7]Tang X., Zhao Y., Yu H., et al., Concentration-regulated multi-color fluorescent carbon dots for the detection of rifampicin, morin and Al 3+ [J].Mater.Today Adv.,2023,18:100383.

[0085] (6) Actual sample testing

[0086] Differential pulse voltammetry was used to detect the content of rifampicin in commercially available rifampicin eye drops and serum. Using the standard addition method, a certain amount of rifampicin standard was added to calculate the sample spike recovery. The test results are shown in Table 2. The average spike recovery of rifampicin samples was 98.43% to 102.00%, and the relative standard deviation (RSD) was 1.07% to 3.49%, indicating that this method is reliable and can be applied to the actual detection of rifampicin in rifampicin eye drops and serum.

[0087] Table 2 Sample content determination and spike recovery (n = 3)

[0088]

[0089]

[0090] (7) Reproducibility, stability, and anti-interference

[0091] In order to evaluate the reproducibility of the sensor prepared by the present invention, five newly modified NiIn 2 O 4 / CeO 2 / GCE was used to measure the oxidation peak current signal under the same conditions, and its RSD was 3.47%, indicating that the sensor has high reproducibility. -1 In rifampicin, the DPV method was used to repeat the test 10 times, and the RSD of a series of current values ​​was 1.04%. Subsequently, the sensor was stored in a refrigerator at 4°C for 1 month, and the current was still 90.1% of the initial current value. The results show that the sensor has good short-term and long-term stability.

[0092] Anti-interference is an important characteristic of the sensor. 2 O 4 / CeO 2 When measuring rifampicin under / GCE, some interfering substances that may exist in the actual sample were added (glucose, starch, urea, cysteine, histidine, phenylalanine, ascorbic acid, leucine, Fe 2+ , K + 、Co 2+ 、Na 2+ , oxytetracycline hydrochloride, epinephrine, glutathione, caffeic acid, artemisinin, luteolin, nifedipine), and studied the degree of interference in the presence of 100-fold concentration of substances. The relative errors of the current before and after the addition of interfering substances were within ±5%, indicating that the presence of these substances did not significantly affect the detection of rifampicin, and the sensor had good selectivity.

[0093] In summary, the present invention adopts an in-situ polymerization method to prepare a NiIn 2 O 4 / CeO 2 / GCE composite material detection platform, and successfully applied to the rapid, sensitive and selective detection of rifampicin. The results showed that the composite material has electrocatalytic activity for the electrochemical oxidation of rifampicin. The sensor is sensitive to rifampicin concentrations in the range of 0.02 to 82.5 μmol·L -1 It has a good linear relationship in the range and the detection limit is as low as 2.54nmol·L -1 This unique structure of NiIn 2 O 4 / CeO 2 The GCE / GCE electrochemical sensor has good reproducibility, high stability and excellent selectivity, providing a promising strategy for the analysis of rifampicin in drugs.

[0094] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art may make some modifications and improvements without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be based on the definition of the claims.

Claims

1. A method for preparing a NiIn2O4 / CeO2 composite material, characterized in that: The steps include: (1) DMF and pyridine are mixed evenly, and then indium nitrate hydrate and terephthalic acid are added, and then stirred after ultrasonication to disperse evenly, and the reaction is continued at 110-130° C. for 20-40 minutes. After the reaction is completed, the suspension is taken out, and the suspension is cooled to room temperature, and the substrate is centrifuged to obtain the substrate, and the obtained precipitate is washed, dried, and calcined to obtain In2O3; (2) In2O3 and Ni(NO3)2·6H2O are placed in a container, anhydrous ethanol is added, ultrasonic dispersion is carried out, and the mixture is refluxed at 85-95°C for 1-2 hours under continuous stirring. After the reaction is completed, the suspension is cooled to room temperature, the substrate is obtained by centrifugation, the obtained precipitate is washed, dried, and calcined to obtain NiIn2O4; (3) NiIn2O4 is placed in a container, ethanol aqueous solution is added, ultrasonic dispersion is uniform, cerium nitrate solution and urotropine solution are added, and the mixture is kept at 50-70°C for 1-3 hours. The substrate is separated by centrifugation, the precipitate is washed, and dried to obtain a NiIn2O4 / CeO2 composite material.

2. The method for preparing the NiIn2O4 / CeO2 composite material according to claim 1, characterized in that: The specific operation steps of step (1) are as follows: 300-500 mL DMF and 0.5-0.6 mL pyridine are added into a container and mixed evenly, and then 0.5-0.8 g indium nitrate hydrate In(NO3)3·xH2O and 0.5-0.8 g terephthalic acid C8H6O4 are added, ultrasonicated for 3-8 min, stirred for 20-40 min to make it evenly dispersed, and reacted at 100-150° C. for 20-50 min; after the reaction is completed, the suspension is taken out and cooled to room temperature, and the suspension is heated at 4000-6000 r·min. -1 After centrifugation for 3-8 minutes, the substrate was taken out and the precipitate was washed with water and ethanol for 2-5 times respectively, dried in a vacuum oven at 50-70℃ for 2-5 hours to obtain a white powder, which was then calcined at 3-8℃·min -1 The temperature was raised at a rate of 110-130 °C for 1-3 h, then calcined at 400-600 °C for 1-3 h, and then at 3-8 °C·min -1 The temperature was cooled to room temperature at a rate of to obtain light yellow powder In2O3.

3. The method for preparing the NiIn2O4 / CeO2 composite material according to claim 1 is characterized in that the specific operation steps of step (2) are as follows: 90-110 mg In2O3 and 130-160 mg Ni(NO3)2·6H2O are placed in a container, 40-60 mL anhydrous ethanol is added, ultrasonicated for 15-30 min to make them evenly dispersed, and refluxed at 85-95°C for 1-2 h under continuous stirring; after the reaction is completed, the suspension is cooled to room temperature and 6000-9000 r·min -1 After centrifugation for 3-8 minutes, the substrate was taken out and the precipitate was washed with water and ethanol for 2-5 times, then dried in a vacuum drying oven at 50-70°C for 2-5 hours to obtain a gray-green powder, which was calcined in a tube furnace at 3-8°C·min under a N2 atmosphere. -1 Increase the temperature at a rate of 300-400℃ for 40-80min, close the N2 valve, and calcine at 300-400℃ for 40-80min in air at 3-8℃·min -1 The temperature was cooled to room temperature to obtain NiIn2O4.

4. The method for preparing the NiIn2O4 / CeO2 composite material according to claim 1, characterized in that: The specific operation steps of step (3) are as follows: weigh 40-60 mg NiIn2O4 and place it in a container, add 50-80 mL 50% ethanol aqueous solution, ultrasonicate for 8-15 min to make it dispersed evenly, and slowly add 8-15 mL 3-8 mmol·L -1 8-15mL of cerium nitrate solution and 10-20mmol·L -1 Hexamethylenetetramine solution, maintained at 50-70℃ for 1-3h, 6000-9000r·min -1 The mixture was centrifuged for 3-8 minutes, and the substrate was separated by centrifugation. The precipitate was washed with water and ethanol for 2-5 times, respectively, and dried in vacuum at 50-70°C for 2-5 hours to obtain a NiIn2O4 / CeO2 composite material.

5. Application of the NiIn2O4 / CeO2 composite material prepared by any one of the preparation methods of claims 1 to 4 in the detection of rifampicin, characterized in that: The NiIn2O4 / CeO2 composite material is used to prepare a corresponding electrochemical sensor, and the electrochemical sensor is used to detect the content of rifampicin.

6. The use according to claim 5, characterized in that: The method for detecting the content of rifampicin includes detecting the content of rifampicin in rifampicin eye drops and blood samples.

7. The use according to claim 5, characterized in that: The preparation of the electrochemical sensor comprises the following steps: using water to prepare a NiIn2O4 / CeO2 composite material to form a 0.8-1.2 mg·mL -1 The NiIn2O4 / CeO2 composite material suspension is prepared; the glassy carbon electrode is polished, cleaned, and blown dry with N2, and then the NiIn2O4 / CeO2 composite material suspension is dropped on the surface of the glassy carbon electrode and dried naturally to obtain a NiIn2O4 / CeO2 composite material modified electrode as the electrochemical sensor.

8. The use according to claim 7, characterized in that: The detection steps of the rifampicin content are as follows: inserting the NiIn2O4 / CeO2 composite material modified electrode into the test solution, incubating for 20 seconds, and then using differential pulse voltammetry to detect the rifampicin content.

9. The use according to claim 8, characterized in that: When detecting the content of rifampicin in a drug, the preparation method of the test solution is as follows: the drug is added to a PBS buffer solution with a pH of 1-3 to prepare a solution containing 0.02 to 82.5 μmol·L -1 The rifampicin concentration is tested after the base solution; When detecting the content of rifampicin in a blood sample, the preparation method of the test solution is as follows: serum and anhydrous methanol are taken at a V / V ratio of 1:3, mixed thoroughly and evenly, centrifuged to remove plasma protein precipitation, and the supernatant is taken and added with a PBS buffer solution of pH=1-3 for testing.

10. The use according to claim 9, characterized in that: The medicine is rifampicin eye drops, and the pH of the PBS buffer is 2.5.

Citation Information

Cited By

  • MOF-derived In2O3-CeO2 composite material based on adsorption cotton template, gas sensor, preparation and application

    CN122187117A